HUBUNGAN ANTARA DURASI BATUK PILEK DENGAN KEMAMPUAN MOTORIK KASAR PADA ANAK-ANAK - Adnan Faris Naufal; Zahra Almadani; Wahyu Tri Sudaryanto; Diki Retno Yuliani (Physio Journal, 2023)
Background: Common cold often seen as a trivial disease, but for babies as well as children under 5 old, this disease can cause more severe cases, one of which is a decrease in gross motor skill. Even though children’s motor skill is fundamental for the next life. Purpose: The purpose of this study whether there is a relationship between the duration of a common cold and gross motor skill in children. Methods: This study used a cross-sectional study design with a population is all of children with common cold case, age 2 mounths-5 years at Fisioterapi Center and Baby Spa Atik Hidayati Clinic. The sample in this study amounted to 62 respondents who were taken using the accidental sampling technique. The instruments used were common cold questionnaire and ASQ-3 and then analyzed it by univariate and bivariate using the Spearman’s Rho correlation test. Results: The results of the bivariate analysis showed tata there was no relationship between the duration of common cold and gross motor skill Sig. (2-tailed) 0,226. Most of respondents was at age of 2 months-1 years (40,3%), most of them (53,3%) ere male. The duration of common cold was dominated by acute duration (85,5%) with 83.9% gross motor skill above average. Conclusion: This study has not been able to show a relationship between the duration of a common cold and gross motor skill in children.